Antiproliferative and cytotoxic effects of sesquiterpene lactones isolated from Ambrosia artemisiifolia on human adenocarcinoma and normal cell lines - Balázs Kovács; Nikoletta Szemerédi; Norbert Kúsz; Tivadar Kiss; Boglárka Csupor-Löffler; Yu-Chi Tsai; Bálint Rácz; Gabriella Spengler; Dezső Csupor (Taylor & Francis Group, 2022)
Context Ambrosia artemisiifolia L. (Asteraceae) contains sesquiterpene lactones as characteristic secondary metabolites. Many of these compounds exert antiproliferative and cytotoxic effects.Objective To isolate the sesquiterpene lactones from the aerial part of A. artemisiifolia and to elucidate their cytotoxic, antiproliferative and antibacterial effects.Materials and methods The compounds were identified by one-dimensional (1D) and 2D NMR, HR-MS spectroscopy from the methanol extract. Isolated compounds were investigated for their cytotoxic and antiproliferative effects on human colonic adenocarcinoma cell lines and human embryonal lung fibroblast cell line using MTT assay. The selectivity of the sesquiterpenes was calculated towards the normal cell line. To check the effect of drug interactions between compounds and doxorubicin, multidrug-resistant Colo 320 cells were used.Results A new seco-psilostachyinolide derivative, 1,10-dihydro-1'-noraltamisin, and seven known compounds were isolated from the methanol extract. Acetoxydihydrodamsin had the most potent cytotoxic effect on sensitive (Colo205) cell line (IC50 = 7.64 µM), also the strongest antiproliferative effect on Colo205 (IC50 = 5.14 µM) and Colo320 (IC50 = 3.67 µM) cell lines. 1'-Noraltamisin (IC50 = 8.78 µM) and psilostachyin (IC50 = 5.29 µM) showed significant antiproliferative effects on the multidrug-resistant Colo320 cell line and had moderate selectivity against human embryonal lung fibroblast cell line. Psilostachyin C exhibited cytotoxic effects on Colo205 cells (IC50 = 26.60 µM). None of the isolated compounds inhibited ABCB1 efflux pump (EP; P-glycoprotein) or the bacterial EPs.Discussion and conclusions Acetoxydihydrodamsin, 1'-noraltamisin, and psilostachyin showed the most remarkable cytotoxic and antiproliferative activity on tumour cell lines and exerted selectivity towards MRC-5 cell line.